SPECTRAL CHARACTERISTICS OF TWO PARAMETER FIFTH DEGREE POLYNOMIAL CONVOLUTION KERNEL - Milivojević , Zoran; Savić, Nataša; Prlinčević, Bojan (Bulletin of Natural Sciences Research, 2022)
In this paper, the spectral characteristic of a polynomial two parameter convolutional fifth - order interpolation kernel is determined. The spectral characteristic is determined as follows. First, the kernel is decomposed into components. After that, the spectral characteristics of each kernel component were calculated using the Fourier transform. Finally, the spectral characteristic of the interpolation two parameter kernel using a combination of the spectral components of the kernels and the kernel parameters, α and β, is formed. Through a numerical example and a graphical representation of the spectral characteristics of the one parameter and two parameter kernels, greater similarity of the spectral characteristics of the 2 P kernel, relative to the ideal box characteristic, is shown.